2001
DOI: 10.1074/jbc.m008483200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Critical Stripe Residues in Transmembrane Span 7 of the Serotonin Transporter

Abstract: Mutations at critical residue positions in transmembrane span 7 (TM7) of the serotonin transporter affect the Na ؉ dependence of transport. It was possible that these residues, which form a stripe along one side of the predicted ␣-helix, formed part of a water-filled pore for Na ؉ . We tested whether cysteine substitutions in TM7 were accessible to hydrophilic, membrane-impermeant methanethiosulfonate (MTS) reagents. Although all five cysteine-containing mutants tested were sensitive to these reagents, noncyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…1) and the same conclusion was reached in SERT (21). In this gene family cysteine substitution was quite well tolerated in other TMDs and loops (17,28,32). It appears therefore that the heavily impacted external half of TMD I fulfils an important role in neurotransmitter transport in line with previous observations on its importance in the interaction with the neurotransmitter (18,19).…”
Section: Discussionsupporting
confidence: 63%
“…1) and the same conclusion was reached in SERT (21). In this gene family cysteine substitution was quite well tolerated in other TMDs and loops (17,28,32). It appears therefore that the heavily impacted external half of TMD I fulfils an important role in neurotransmitter transport in line with previous observations on its importance in the interaction with the neurotransmitter (18,19).…”
Section: Discussionsupporting
confidence: 63%
“…Together with data from the F380Y mutant of SERT (24), the present data suggest that for SERT also, Na ϩ induces a conformational change or stabilizes the native conformation of SERT to oppose the conformational change induced by Li ϩ . In previous studies Li ϩ has been used as an inert replacement for Na ϩ (4,13,14).…”
Section: Discussionmentioning
confidence: 73%
“…2 We consider it more likely that Na ϩ and Li ϩ , acting at different sites, both induce conformational changes in the transporter and that these changes are mutually exclusive. Recent results with the F380Y mutant of SERT indicates the opposing effects of Na ϩ and Li ϩ on the reactivity of Cys-109 (24). Another indication of this phenomenon is that Na ϩ and Li ϩ had opposite effects on ␤-CIT binding to SERT (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The important role of TM1 was supported by the suggestion of G100 as a structural pivot providing flexibility during substrate translocation (33). In TM7, several residues are important for uptake and Na ϩ dependence, indicating that TM7 is involved in binding pocket formation or substrate translocation (34). A cysteine scanning of residues in TM3 indicated that Ile 172 and Tyr 176 are associated with a 5-HT and cocaine binding pocket (35).…”
mentioning
confidence: 77%